The Role of Artificial Intelligence in Managing Scientific Research Projects Funded by KEGA and VEGA Grant Schemes - Bočková, Kateřina; Procházka, David Anthony; Bartoš, Pavel (Journal of Ecohumanism, 2025)
The article examines the application of Artificial Intelligence (AI) in managing scientific and educational projects funded by the KEGA and VEGA grant schemes in Slovakia. The objective is to analyse how AI contributes to more efficient management of project processes, including the initiation, planning, implementation, monitoring, and closure of projects. Research identifies key areas where AI provides significant benefits, such as automation of administrative tasks, optimisation of resource allocation, and decision-making support through predictive analysis. The article also highlights the utilisation of AI tools, such as chatbots and advanced machine learning algorithms, to improve communication and monitoring project activities. The findings indicate that AI not only facilitates the complex grant management but also improves the quality of achieved outcomes. Despite these positive contributions, the research has revealed several challenges, including insufficient integration of AI in certain phases of the project lifecycle and concerns about the ethical use of these technologies. Recommendations include the need to further education of project managers in AI-related areas and the development of strategies for their effective implementation. The article offers a fresh perspective on the use of AI in project management and introduces valuable tools and methodologies that can help project teams in achieving superior results.